Letter from Jack Jackson to Jane Tolmach - Jack Jackson:::::: (1973)
A letter from Jack Jackson from the Massachusetts Mutual Life Insurance Company to Jane Tolmach congratulating her on her election to the position of Mayor of Oxnard.